2016
DOI: 10.5946/ce.2016.020
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Tuberculous Mediastinal Lymphadenitis, with an Esophagomediastinal Fistula, Mimicking an Esophageal Submucosal Tumor

Abstract: Mediastinal tuberculous lymphadenitis rarely mimics esophageal submucosal tumor, particularly in the case of multidrug-resistant tuberculosis (MDR-TB). Herein, we report the case of a 61-year-old woman who visited a local hospital complaining of odynophagia. An initial esophagogastroduodenoscopy revealed an esophageal submucosal tumor, and subsequent chest computed tomography showed subcarinal lymphadenopathy with an esophagomediastinal fistula. The patient was then referred to Samsung Medical Center, and a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The usual presenting symptoms are dysphagia or odynophagia[2]. There are several reports on esophageal TB that appeared as submucosal lesions mimicking a mass, ulcer, diverticulum, or only sinus opening[1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The usual presenting symptoms are dysphagia or odynophagia[2]. There are several reports on esophageal TB that appeared as submucosal lesions mimicking a mass, ulcer, diverticulum, or only sinus opening[1].…”
Section: Discussionmentioning
confidence: 99%
“…Mediastinal tuberculosis (TB) lymphadenitis is a rare clinical manifestation of TB in adults, and it usually occurs secondary to pulmonary TB. Extrapulmonary lymph node TB was reported to be 17.6% of all TB cases[1]. Esophagomediastinal fistula formation secondary to mediastinal TB lymphadenitis is an unusual complication that develops as a consequence of erosion of adjacent organs[2].…”
Section: Introductionmentioning
confidence: 99%
“…MDR-TB lymphadenitis is a rare manifestation of a disease of significant public health concern. While there have been reported cases of MDR-TB lymphadenitis in TB endemic regions of the world [ 3 - 4 ]; cases of MDR-TB lymphadenitis represent an unusual and atypical presentation of the disease in the US.…”
Section: Discussionmentioning
confidence: 99%
“…With current advancements in therapy, extra-pulmonary forms of MDR-TB are rare and are uncommon presentations of the disease; however, they appear to be on the rise [ 1 ]. There have been few cases of MDR-TB lymphadenitis presented in the literature [ 3 - 4 ]. We present a case of a 22-year-old human immunodeficiency virus (HIV) negative female who presented with cervical lymphadenopathy and sinus discharge at the site of the involved lymph nodes and was diagnosed with MDR-TB.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rates of tuberculous mediastinal lymphadenitis are 5% to 17.6% of total TB cases and decreased with the increasing of age. [ 14 , 15 ] Although, it is usually asymptomatic, the symptoms was reported that lymph nodes compresses upon adjacent structures. [ 4 ] The sensitivity of CT scanning on tuberculous lymphadenitis is 57% in total.…”
Section: Discussionmentioning
confidence: 99%